Uso de complexo enzimático em dietas para tilápia do Nilo: digestibilidade, atividade enzimática, desempenho produtivo e parâmetros fisiológicos - Pereira, Bruno Henrique Silva [UNESP] (2014)
The inclusion of enzyme supplement in fish diets is a promising strategy to increase the feed efficiency. This work aimed to evaluate the effect of inclusion of the enzymatic complex (Allzyme SSF) on apparent digestibility and non-specific protease activity in juvenile Nile tilapia. Six levels of inclusion of the enzymatic complex were evaluated (0; 0.025; 0.040; 0.055; 0.070 and 0.085%). A total of 486 fish were distributed in 18 feeding aquaria and 18 tanks of faeces collection (modified Guelph system). After 10 and 20 days of feeding, four fish per aquarium were collected and the anterior portion of the intestine were sampled. The experimental design was completely randomized with six treatments and four replicates. There was no significant difference in the apparent digestibility coefficients (ADCs) of protein, gross energy and protease activity among the tested levels of inclusion and periods. Under the conditions evaluated the inclusion of the enzymatic complex did not improve the digestibility of diets in juvenile Nile tilapia